International perspectives on cyberbullying - Random Publications
Cyberbullies use the anonymity that the internet provides to continuously provoke and taunt an individual or group of individuals. This book brings together an international group of experts to present the latest psychosocial and developmental criminological research on cyberbullying, cybervictimization and intervention. Cyberbullying derives from bullying, which is defined loosely as "any unwanted behavior". It involves intentionally putting down another person, threatening another person, joking on another person, and making that person feel worthless via electronic means. Most people who think of cyberbullying generally only think of another person ganging up on another person through Facebook or twitter. It is way more than that. Sending a text to a friend telling them something mean about another person is also cyberbullying. Downgrading other players on Xbox is also cyberbullying. Creating a fake profile to intentionally trick/harass someone is cyberbullying. Even though most of these things are done anonymously and it may never get back to that person it is intentionally putting someone down via electronics. The aim of this study was to gain a better understanding of the impact of cyber bullying on students and the possible need for prevention messages targeting students, educators and parents.